Bisphenol A Induces Apoptosis in Liver Cells through Induction of ROS. (11th February 2015) - Kourouma, Ansoumane; Quan, Chao; Duan, Peng; Qi, Suqin; Yu, Tingting; Wang, Yinan; Yang, Kedi
Abstract : Oxidative stress mechanisms are involved in hepatotoxicity. The liver is reported to be affected by bisphenol A (BPA) in animals studies and has been also reported to possess hepatic toxicity. This study aimed to examine association between liver health status and the effects of BPA on the antioxidant defense systems and liver biomarkers. BPA (0, 2, 10, and 50 mg/kg) body weight was mixed in corn oil and intraperitoneally administered every forty-eight hours for 30 days in dose-dependent manner. There was no significant difference between the body weight and weight of rat liver in BPA-treated groups and control groups. The study results show that the levels of malondialdehyde (MDA) and hydrogen peroxide (H2 O2 ) increased after exposure to BPA. However, the antioxidant enzymes catalase (CAT), superoxide dismutase (SOD), and glutathione peroxidase (GSH-PX) were significantly (P < 0.001, P < 0.05, andP < 0.001, resp.) decreased at 50 mg/kg dosage. Liver markers activities such as lactate dehydrogenase (LDH), glutamic-oxalacetic transaminase (GOT), and glutamic-pyruvic transaminase (GPT) were significantly increased, while γ -glutamyl transferase ( γ -GT) activity was decreased. BPA exposure increased activity of liver biomarkers indicating liver hyperactivity. Analysis of the liver section provided essential evidence of liver apoptosis. Moreover, BPA may lead to induced toxic response of liver oxidative system.